What Factors of the Teaching and Learning Environment Support the Learning of Generic Skills? First-Year Students’ Perceptions in Medicine, Dentistry and Psychology - Räisänen, Milla; Pyörälä, Eeva; Tuononen, Tarja (Frontiers in Education, 2022)
Future health professions need generic skills in their working lives, such as knowledge analysis, collaboration, communication and problem-solving skills. The teaching and learning environment is crucial in the development of generic skills when studying at university. The aim of this research was to examine students’ perceptions of learning generic skills during their first study year and how the teaching and learning environment related to their learning experiences perceptions. The data were collected from first-year students (medicine n=215, dentistry n=70 and psychology n=89) who completed a questionnaire at the end of their first study year. Two cohorts of first-year students from 2020 and 2021 were combined. The teaching and learning environments in medicine, dentistry and psychology differed from each other. The results showed that learning of problem-solving, communication and collaboration skills were emphasized more among medical and dental students, whereas analytical skills more among psychology students. There were no statistically significant differences in perceptions of the teaching and learning environment. Perceptions of generic skills and the teaching and learning environment were positively related to each other. In medicine, the strongest predictors of generic skills were peer support and feedback and in dentistry, peer support, interest and relevance. In psychology, the strongest predictors were interest and relevance. The results emphasize the relevance of the teaching and learning environment in learning generic skills.